2018
DOI: 10.1177/0306624x18818810
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Victimization and Fear of Crime on the Legal Socialization of Young Adolescents in São Paulo, Brazil

Abstract: It is important to understand how young adolescents come to view authorities during formative years. Experiencing, witnessing, and fearing victimization have been linked to the process of legal socialization and subsequent attitudes and behavior. In addition, procedural justice may influence adolescent perceptions of fairness of the authorities. The present study tested whether procedural justice mediated and moderated the relationship between young adolescents’ direct and vicarious victimization and developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
0
10
0
2
Order By: Relevance
“…There are notable developments in using existing longitudinal cohort data or collecting new data to evaluate a variety of criminological topics. For example, Murray et al (2015) utilized the 1993 to examine the childhood predictors of violence in late adolescence, the São Paulo Legal Socialization Study was designed to measure and evaluate the development of attitudes towards the law and police among early adolescents (Medina & Rodrigues, 2019;Trinkner et al 2019), and the Evidence for Better Lives Study is a crosscultural birth cohort study that aims to examine the effects of prenatal exposure to violence on mothers and childhood development (Valdebenito et al, 2020).…”
Section: Single-country Datamentioning
confidence: 99%
“…There are notable developments in using existing longitudinal cohort data or collecting new data to evaluate a variety of criminological topics. For example, Murray et al (2015) utilized the 1993 to examine the childhood predictors of violence in late adolescence, the São Paulo Legal Socialization Study was designed to measure and evaluate the development of attitudes towards the law and police among early adolescents (Medina & Rodrigues, 2019;Trinkner et al 2019), and the Evidence for Better Lives Study is a crosscultural birth cohort study that aims to examine the effects of prenatal exposure to violence on mothers and childhood development (Valdebenito et al, 2020).…”
Section: Single-country Datamentioning
confidence: 99%
“…As evidenced by research (Boney-McCoy & Finkelhor, 1995;Chang et al, 2003;Hughes et al, 2015;Medina & Rodrigues, 2019;Shaffer & Ruback, 2002;Sharkey et al, 2012), there has been a historical focus on understanding the relationship between victimization, maltreatment, and child abuse with maladaptive behavior. With this background in mind, victimization in our study was examined in three areas: home, school, and neighborhood, and included a focus on a range of behaviors by the perpetrator that encompassed treating others cruelly and unfairly (see specific questions under "Measures" in the Method section below) and considered both direct and indirect impact.…”
Section: Victimizationmentioning
confidence: 99%
“…It has been suggested that recognition of legitimacy or its lack informs the choices that children, adolescents, and adults make to comply or not with norms and rules Thomas et al, 2018;Trinkner et al, 2012). While there are documented and expected reasons for a decline in parental legitimacy (PL) in areas of personal domain such as choosing friends or what clothes to wear (Darling et al, 2008), there are individual factors that need to be further investigated, such as the role victimization plays in PL (Medina & Rodrigues, 2019).…”
mentioning
confidence: 99%
“…Victimization has also been related to at-risk youths' evaluations of police effectiveness and personal morality: those victimized tend to feel that the police have failed to protect them, and that the police are ineffective and illegitimate and therefore do not deserve cooperation ) Sargeant & Kochel, 2018;Slocum et al, 2010;Wu et al, 2015). As well, victimized youth tend to morally justify deviant behavior ) Doering & Baier, 2016;Medina & Rodrigues, 2019(.…”
Section: Policing Youth At Riskmentioning
confidence: 99%